2004
DOI: 10.1179/026708304225019821
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural analysis of varistors prepared from nanosize ZnO

Abstract: ZnO nanoparticles were prepared by a solid state pyrolysis reaction of zinc acetate dihydrate and oxalic acid dihydrate at 500uC. The course of reaction at various temperatures was followed by XRD. Subsequently varistors were fabricated from this nano-ZnO material by solid state mixing with various oxide additives and sintering to 1050uC. The microstructure of the sintered material was studied using XRD, field emission SEM (FESEM), and EDX, and ZnO grains, bismuth rich regions and spinel phases were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
(20 reference statements)
1
33
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] The electrical conductivity of ZnO is controlled by intrinsic defects such as oxygen vacancies and/or zinc interstitials, which act as ntype donors. When doped with group III elements such as indium, boron, gallium and aluminum the electrical resistivity decrease.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The electrical conductivity of ZnO is controlled by intrinsic defects such as oxygen vacancies and/or zinc interstitials, which act as ntype donors. When doped with group III elements such as indium, boron, gallium and aluminum the electrical resistivity decrease.…”
Section: Introductionmentioning
confidence: 99%
“…S1b. In addition, EG is widely known to act as a chelating agent and has been used in metal oxalate studies to extend the lengths of rod-like structures or assist the structural growth of complexes in a one-dimensional fashion13192021. Interestingly, however, we found that EG does not help 1 to grow lengthwise, but instead helps the structure to grow two-dimensionally in sheets.…”
mentioning
confidence: 62%
“…3 It can also be used in the fabrication of gas sensors, varistors, and piezoelectronic devices. [4][5][6] The properties of zinc oxide have been under investigation for decades. 7 The shift from bulk to nanosized materials has introduced new electronic and optical properties due to surface effects, defect formations, and quantum confinement.…”
Section: Introductionmentioning
confidence: 99%